Early Parental Eating Messages and Disordered Eating: The Role of Body Shame and Inflexible Eating - Oliveira, Sara (2019)
The current study tested a path model that examined the association between early caregiver eating messages (restrictive and pressure to eat) and current disordered eating and whether body image shame and inflexible eating mediate this relationship, in a sample of 433 women aged from 18 to 40. Correlation analyses showed that the recall of restrictive/critical caregiver eating messages is linked to body image shame, inflexible eating and disordered eating. Path analysis results indicated the plausibility of the tested model, which accounted for 70% of the variance of disordered eating. Findings suggested that women who recall more restrictive/critical caregiver eating messages tend to present more body image-focused shame experiences and to adopt more inflexible eating rules and, consequently, engage in disordered eating and behaviors. This study contributes to a better understanding of the impact of early caregiver eating messages on disordered eating behaviors and also emphasizes the impact of maladaptive emotions and strategies, such as body image shame and adherence to inflexible eating rules on the display of disordered eating. Therefore, this paper may offer important insights for future research and for the development of intervention programs.